A Vygotsky’s sociocultural approach to understanding pre-service English teachers for professional development (a study at STKIP PGRI Bangkalan) - Ridwan, Arfiyan (Penerbit STKIP PGRI Bangkalan, 2019)
The Pre-service teacher program is a compulsory subject at STKIP PGRI Bangkalan with the aim of giving students a real experience to do the learning process in class. Pre-service teacher program itself is divided into 2 courses, namely Pre-service teacher program I (where students are trained to make learning plans on campus followed by microteaching) and Pre-service teacher program II (where students are actually deployed to schools for real teaching practices. This research aims to analyze the extent to which the Pre-Service Teacher Program has contributed to the development of professionalism of prospective teachers or preservice teacher professional development from the perspective of Vygotsky's sociocultural theory. The perspectives to be used in this study are genetic law of development, zone of proximal development, and mediation. Students as prospective teachers must develop themselves in this practicum before they become real teachers (in-service teacher). There are three pre-service students involved in this study in different schools. The data was obtained through document collection, mainly lesson plans, and through interview. The results show that there is an apparent progress in between the two courses of preservice teacher program in terms of pedagogical skills. The mediation between mentor teacher and lecturer supervisor opened a great opportunity for sharing knowledge and ideas in teaching. The pre-service teachers were benefited through sharing of in-service teachers’ experiences, whereas the in-service teachers were benefited through pre-service teachers’ fresh ideas in teaching.